Characterisation of a novel reverse-biased PPD CMOS image sensor. (7th November 2017) - Stefanov, K.D.; Clarke, A.S.; Ivory, J.; Holland, A.D.
Abstract: A new pinned photodiode (PPD) CMOS image sensor (CIS) has been developed and characterised. The sensor can be fully depleted by means of reverse bias applied to the substrate, and the principle of operation is applicable to very thick sensitive volumes. Additional n-type implants under the pixel p-wells, called Deep Depletion Extension (DDE), have been added in order to eliminate the large parasitic substrate current that would otherwise be present in a normal device. The first prototype has been manufactured on a 18 μ m thick, 1000 Ω  .cm epitaxial silicon wafers using 180 nm PPD image sensor process at TowerJazz Semiconductor. The chip contains arrays of 10 μ m and 5.4 μ m pixels, with variations of the shape, size and the depth of the DDE implant. Back-side illuminated (BSI) devices were manufactured in collaboration with Teledyne e2v, and characterised together with the front-side illuminated (FSI) variants. The presented results show that the devices could be reverse-biased without parasitic leakage currents, in good agreement with simulations. The new 10 μ m pixels in both BSI and FSI variants exhibit nearly identical photo response to the reference non-modified pixels, as characterised with the photon transfer curve. Different techniques were used to measure the depletion depth in FSI and BSI chips, and the results are consistent with the expected full depletion.